Patient-reported experiences on supportive care strategies following the introduction of the first Swedish national cancer strategy and in accordance with the new patient act. (4th March 2018) - Westman, Bodil; Kirkpatrick, Lily; Ebrahim, Fereshte; Henriksson, Roger; Sharp, Lena
Abstract: Introduction: Several supportive care strategies are described in Swedish legislation and policy documents, such as the National Cancer Strategy and the Patient act. No previous systematic evaluation from a patient perspective has been performed. The aim of this study was to evaluate how these supportive care strategies are experienced by patients treated for cancer in the Stockholm-Gotland region. Material and methods: In this cross-sectional study, we identified patients (diagnosed with gynaecological, haematological, upper gastrointestinal and head and neck cancer during 2014) from the Swedish Cancer Register. The European Organization of Research and Treatment of Cancer, EORTC, Quality of Life Questionnaires, QLQ-C30, Information QLQ-INFO25 and a study-specific questionnaire was used to collect data during follow-up after cancer treatment. We collected data on 869 cancer patients' perception of availability and access to supportive care strategies and how they were experienced. Results: Among the supportive care strategies suggested in the legislation and policy documents, just over half of the patients ( n  = 393, 53%) reported that they had access to a contact nurse, while 43% ( n  = 312) had received an individual written care plan and 16% ( n = 137) had been referred to palliative care. Only 29% ( n  = 218) of the patients reported that they had received information about patient advocacy groups and 8% ( n = 62) on medical second opinions from their cancer care team. Discussion: The supportive care strategies suggested in Swedish legislation and policy documents may be useful but are only available for some patients. The implementation goals for the National Cancer Strategy and the Swedish Patient act have not been reached.